Answer:
and
![y=1](https://img.qammunity.org/2020/formulas/mathematics/high-school/shmuyul9qjj9r1nqzr15kdsrv22lgw6ocn.png)
Explanation:
We have to solve by substitution the given system of equations:
![\left \{ {{(3)/(8)x+(1)/(3)y=(17)/(24) }\atop {x+7y=8}} \right.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jgwii8nbocib38mhektrjb44z4avh34kee.png)
First, we have to choose an equation, no matter which one, and isolate a certain variable, no matter which one either. So, by our own criteria, we choose the second equation, and we'll isolate x:
![x+7y=8\\x=8-7y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6sln6hqrlp3vgtnafz6q6kxrgllyqjx3jw.png)
Now, this equivalence for x, we will replace it in the other equation, instead of x, we will put the result:
![(3)/(8)(8-7y)+(1)/(3)y=(17)/(24)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dcjlfxus8m735x4xgp2ojqwns54gnv7w7o.png)
Then, we solve for y:
![(3)/(8)(8-7y)+(1)/(3)y=(17)/(24)\\(3)/(8)8-(3)/(8)7y+(1)/(3)y=(17)/(24)\\-(21)/(8)y+(1)/(3)y=(17)/(24)-3\\(-63y+8y)/(24)=(17-72)/(24)\\ (-55y)/(24)=(-55)/(24)\\y=(-55(24))/(24(-55))=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eg6gnhkvy7xpbv8xguha33cu9pqdeto53o.png)
Now, the final process will be to replace this y-value in one equation, no matter which one, and find x-value:
![x+7y=8\\\\x+7(1)=8\\x=8-7\\x=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cnyd6fbdq3l8j2wdlbwcgyixxddszympnj.png)
Therefore, the solution of the system is
and
![y=1](https://img.qammunity.org/2020/formulas/mathematics/high-school/shmuyul9qjj9r1nqzr15kdsrv22lgw6ocn.png)